Model Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Peserta Didik Pasca Pandemi Covid-19 - Laeny Siti Hasanah (UPPM Politeknik TEDC Bandung, 2023)
This study aims to determine the increase in learning outcomes through the Discovery Learning learning model as a learning innovation that can be applied by educators after the Covid-19 pandemic. Through literature review, the